Answer:
A. x = 3, y = -3
B. a = -2, b = 5
C. try your best ill see u later
Explanation:
Okay I'mma state some stuff first 3^a + 3^b = 3^(a+b)
and 3^a/3^b = 3^(a-b)
So first equation 3^3*3^-3=3^0
So second equation 3^3/3^-2 = 3^5
So third equation I dont really know the rule but I'mm just plug in a random number for g, like 2, then solve the thing like a normal equation.
So 3^-3 x f^-3 = 12^2 = 144, f^-3 = 144/(3^-3 or 1/27) = 144 x 27 = 3888
so f^-3 = 3888, f = well its an imaginary number according to calculator so u try your best on the last one